2016
DOI: 10.1007/s00442-016-3696-0
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of vertical soil nutrient heterogeneity, and mean and depth-specific soil nutrient availabilities for tree species richness in tropical forests and woodlands

Abstract: The relative importance of resource heterogeneity and quantity on plant diversity is an ongoing debate among ecologists, but we have limited knowledge on relationships between tree diversity and heterogeneity in soil nutrient availability in tropical forests. We expected tree species richness to be: (1) positively related to vertical soil nutrient heterogeneity; (2) negatively related to mean soil nutrient availability; and (3) more influenced by nutrient availability in the upper than lower soil horizons. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
8
0
1
Order By: Relevance
“…Nonethless, different tree species are shown to associate with either high or low available P (Condit et al., 2013), which is mirrored in trait trade‐offs in tree seedlings across a P gradient (Zalamea et al., 2016). However, the concentration of nutrients with depth can also influence tree species richness with root feedback mechanisms in turn contributing to the cycling of nutrients within the soil profile (Jobbágy & Jackson, 2000; Shirima et al., 2016). The root and soil interactions that shape root function remain an uncertainty in our understanding of how tropical trees acquire available P given the highly heterogeneous soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nonethless, different tree species are shown to associate with either high or low available P (Condit et al., 2013), which is mirrored in trait trade‐offs in tree seedlings across a P gradient (Zalamea et al., 2016). However, the concentration of nutrients with depth can also influence tree species richness with root feedback mechanisms in turn contributing to the cycling of nutrients within the soil profile (Jobbágy & Jackson, 2000; Shirima et al., 2016). The root and soil interactions that shape root function remain an uncertainty in our understanding of how tropical trees acquire available P given the highly heterogeneous soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…The species diversity of each 10 × 10 m grid cell was calculated using the Shannon–Weiner index (H=false∑i=1SNiNlog2NiN, where N i is the number of individuals of the i th species, and N is the total number of individuals of all species) (Magurran, 2004). The availability and heterogeneity of each variable for the 10 × 10 m grid cell were calculated using four measurements from the 2 × 2 m quadrat of each grid cell, the mean of four measurements was used to express soil resource availability, and the coefficient of variation (CV) was employed as the measure of soil resource heterogeneity (Marchand & Houle, 2006; Reynolds et al, 2007; Shirima et al, 2016; Ulrich et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Bartels and Chen (2010) demonstrated that resource availability drives species diversity in both young and mature stands of forest ecosystems, whereas resource heterogeneity dominates in old‐growth stands. Shirima et al (2016) suggested that the mean soil nutrient availability explains considerable variations in tree species richness in moist forests, while vertical soil nutrient heterogeneity is a predictor of tree species richness in miombo woodlands. In fact, species diversity and abundance are scarcely the results of a single factor and direct process, with respect to either resource availability or resource heterogeneity (Whittaker et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The value for richness(R) and species diversity (H') varied among sites (intact and degraded parts of the reserve) and along the topographic gradient as provided in Table 6. The variation in species richness and diversity in such sites could be attributed to physical heterogeneity (Shirima et al, 2016) and anthropogenic perturbation (Yuan et al, 2016). The intact part registers higher species richness and diversity (Table 6).…”
Section: Tree Species Diversitymentioning
confidence: 99%